The roles of microRNAs in horticultural plant disease resistance - Zhang, Aiai; Zhang, Shunshun; Wang, Feng; Meng, Xianmin; Ma, Yue; Guan, Jiantao; Zhang, Feng (Frontiers in Genetics, 2023)
The development of the horticultural plants is largely limited by disease. MicroRNAs constitute a major portion of the transcriptomes of eukaryotes. Various microRNAs have been recognized as important regulators of the expression of genes involved in essential biological processes throughout the whole life cycles of plants. Recently, small RNA sequencing has been applied to study gene regulation in horticultural plants. In this review, we summarize the current understanding of the biogenesis and contributions of microRNA in horticultural plants disease resistance. These microRNAs may potentially be used as genetic resources for improving disease resistance and for molecular breeding. The challenges in understanding horticultural plants microRNA biology and the possibilities to make better use of these horticultural plants gene resources in the future are discussed in this review.